Evaluation of the effect of various cryoprotectants on the resistance of canine erythrocytes to mechanical stress - Hrebeniuk, Karyna; Denysova, Olha (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):245